Safety and Efficacy of Tirofiban During Intravenous Thrombolysis Bridging to Mechanical Thrombectomy for Acute Ischemic Stroke Patients: A Meta-Analysis - Li, Wei; Lin, Guohui; Xiao, Zaixing; Zhang, Yichuan; Li, Bin; Zhou, Yu; Chai, Erqing (Frontiers in Neurology, 2022)
Introduction: The safety and efficacy of tirofiban in intravenous thrombolysis (IVT) bridging mechanical embolization in patients with acute ischemic stroke (AIS) is unknown. The purpose of this meta-analysis was to evaluate the safety and efficacy of tirofiban in IVT bridging mechanical embolization in acute ischemic stroke. Methods: We systematically searched PubMed, Embase, Web of Science, and The Cochrane Library, CNKI, and Wang Fang databases for randomized controlled trials and non randomized controlled trials comparing the tirofiban and non-tirofiban groups in AIS intravenous thrombolysis bridging mechanical thrombectomy (Published by November 20, 2021). Our primary safety endpoints were symptomatic cerebral hemorrhage (sICH), intracranial hemorrhage (ICH), and 3-month mortality; the effectiveness endpoints were 3-month good functional prognosis (MRS ≤2) and successful recanalization rate (modified thrombolytic therapy in cerebral infarction (mTICI) 2b or 3). Results: A total of 7 studies with 1176 patients were included in this Mate analysis. A comprehensive analysis of the included literature showed that the difference between the tirofiban and non-tirofiban groups in terms of successful recanalization rate (OR=1.22, 95% Cl [0.77, 1.91], p=0.4, I2 =22%) and good functional prognosis at 3 months (OR=1.12, 95% Cl [0.82, 1.52], p=0.47, I2=17%) in patients with intravenous thrombolytic bridging mechanical thrombectomy of AIS was not statistically significant. Also, the differences in the incidence of sICH (OR=0.95, 95% Cl [0.57, 1.58], p=0.84) and ICH (OR=0.81, 95% Cl [0.56, 1.18], p=0.27) between the two groups were not statistically significant. However, the use of tirofiban during intravenous thrombolytic bridging mechanical thrombectomy reduced mortality in patients over 3 months (OR=0.54, 95% Cl [0.33, 0.87], p=0.01). Conclusion: The use of tirofiban during intravenous thrombolysis bridging mechanical thrombectomy for AIS does not increase the risk of sICH and ICH in patients and reduces mortality in patients within 3 months. However, this result needs to be further confirmed by additional large-sample, multicenter, prospective randomized controlled trials.